Pelatihan Peningkatan Pengetahuan Masyarakat terhadap Masalah dan Penyebab Gangguan Muskuloskeletal Selama Work from Home dan School from Home saat Pandemi COVID-19 - Dela Fariha Fuadi; Andrew Wijaya Saputra; Putri Karina Syafitri; Cicilia Febriyani Hayuningrum; Nesi (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
One of the consequences of the Covid-19 pandemic is that all activities are carried out at home, both work and study. This causes muscle and joint pain due to public ignorance about the importance of posture and body position during work and study. The purpose of this article is to determine and evaluate the level of public knowledge about the problems and causes of musculoskeletal disorders that arise during Work from Home (WFH) and School from Home (SFH). This community service method uses a quasi-experimental method by giving pre-test and post-test to assess whether there is an increase in knowledge after being given education through online seminars. From a sample of 108 people, it shows that there is an increase in knowledge about the problems and causes of musculoskeletal disorders that arise during Work from Home (WFH) and School from Home (SFH) during the Covid-19 Pandemic.